2022
DOI: 10.3389/fbioe.2022.963996
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass-collagen/poly (glycolic acid) scaffold nanoparticles exhibit improved biological properties and enhance osteogenic lineage differentiation of mesenchymal stem cells

Abstract: Today’s using tissue engineering and suitable scaffolds have got attention to increase healing of non-union bone fractures. In this study, we aimed to prepare and characterize scaffolds with functional and mechanical properties suitable for bone regeneration. Porous scaffolds containing collagen-poly glycolic acid (PGA) blends and various quantities of bioactive glass (BG) 45S5 were fabricated. Scaffolds with different compositions (BG/collagen-PGA ratios (w/w): 0/100; 40/60; 70/30) were characterized for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Possibly, the biomimetic composites were able of stimulating bone metabolism, especially due to osteoconductive properties and ability to attract cells of BG. 11,16 Additionally, the collagenic part possibly served a matrix for sustaining cell growth. Associated to all these positive effects, the BMSCs may have differentiated in pre-osteoblastic cells and osteoblast, which possibly resulted in a higher newly formed bone deposition in the region of the defect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Possibly, the biomimetic composites were able of stimulating bone metabolism, especially due to osteoconductive properties and ability to attract cells of BG. 11,16 Additionally, the collagenic part possibly served a matrix for sustaining cell growth. Associated to all these positive effects, the BMSCs may have differentiated in pre-osteoblastic cells and osteoblast, which possibly resulted in a higher newly formed bone deposition in the region of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 BG, with the composition of 46.1% SiO 2 , 24.4% Na 2 O, 26.9% CaO and 2.6% P 2 O 5 , in mol, is known by its high bioactivity and ability to interact with bone tissue, stablishing a biologically apatite layer, with the release of ions such as silica, calcium and phosphate and stimulation of cell attraction and growth and deposition of newly formed bone. 811…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical applications of the generated scaffolds are constrained since too much glutaraldehyde might have unfavorable toxic effects. , The crosslinking in our proposed formulation is dehydrothermal at high temperature rather than chemical glutaraldehyde application . After optimizing our collagen-based scaffold formulation in terms of the collagen and poly­(glycolic acid) (PGA) ratio in our previous studies, we have reported on autologous bone replacement modalities prepared from human bone marrow MSCs (BM-MSCs) embedded in collagen/PGA (CPGA) scaffolds in laboratory and animal settings. Following an expansion (ex vivo) and osteogenic differentiation induction (short-term), we showed that the BM-MSCs were alive and capable of proliferation and terminal differentiation into osteoblast cells . Furthermore, we successfully tested the bone healing properties of a new tissue engineering cell therapy/scaffold using MSCs derived from rabbit fat tissue embedded in the CPGA scaffold.…”
Section: Introductionmentioning
confidence: 99%